PEMATAHAN DORMANSI BENIH AREN (Arenga pinnata (wurmb.) Merr.) PADA TINGKAT KEMASAKAN YANG BERBEDA MENGGUNAKAN METODE PERENDAMAN - Irwan Mahakam Lesmono Aji; Raden Sutriono; Arna Diansyah (Forestry Study Program University Of Mataram, 2020)
This study aims to find out the effect of submersion by using 1% acetic acid, 100% palm juice, and 100% coconut water to break the dormancy of palm seeds at different maturity levels. The research was conducted in the Green House of Forestry Study Program, University of Mataram, using the experimental method with Complet Random Design (CRD) three factors. The first factor is the maturity level consists of 3 levels, the second factor is the submersion liquid substance consist of 3 levels, and the third factor is the period of submersion consist of 4 levels.The results of this study indicate that maturity rate gives significant influence on the following parameter i.e: percentage potency of seed germination, rotten seed, seed weight, seed moisture content, and embryo lenght, while seed dormancy parameter is not significant. The submersion factor significantly influenced on the following parameter i.e: seed weight, and seed water content, while the other parameters are not significant. The submersion period factor is significant only on seed moisture content and the embryo lenght, while the other parameters have no significant effect. While in all interactions between factors show no significant result on all parameters.